Promoting students' science literacy skills through a simulation of international negotiations: The GlobalEd 2 Project. (January 2018) - ,; Brodowiksa, Kamila; Oren, James; Riel, Jeremy; Song, Shiyu; Wang, Meng; Lawless, Kimberly A.; Brown, Scott W.; Rhoads, Christopher; Lynn, Lisa; Newton, Sarah D.
Abstract: Problem-based learning (PBL) is an instructional design approach for promoting student learning in context-rich settings. GlobalEd 2 (GE2) is PBL intervention that combines face-to-face and online environments into a 12-week simulation of international negotiations of science delegates on global science issues. Although GE2 focuses on science, it is implemented in a social studies classroom. This manuscript describes the GE2 environment and evaluates its impact on middle school students' scientific literacy compared to a comparison group receiving normal educational practice. Hierarchical Linear Modeling (HLM) analyses on GE2 and comparison groups demonstrates the significant positive impact of GE2 on two measures of scientific literacy (Socio-scientific Literacy and Scientific Inquiry), among middle-grade students from two states. Implications regarding instructional practice and future research are discussed. Highlights: Problem-based learning promotes science literacy skills in middle schools. Simulation shows higher socio-science scores than comparison group. Efficacy trials increases socio-science literacy and scientific inquiry skills. Improved students' science skills following a simulation of global water resources.